Strategi Komunikasi Tim Tanggap Bencana UMSU dalam Pemulihan Psikososial bagi Penyintas Pascabencana Alam di Tanjung Pura - Baihaqi Septiansyah Novrizal; Widy Warni Simatupang; Rahmanita Ginting (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the communication strategy of the UMSU Disaster Response Team in the psychosocial recovery process of post-flood survivors in Tanjung Pura, Lalat Regency, with an emphasis on the role of communication in supporting the recovery of the psychological and social conditions of the affected communities. This study uses a qualitative approach with an interpretive case study design. The research data was collected through in-depth interviews with 4 volunteers of the UMSU Disaster Response Team and 4 flood survivors who were selected through purposive techniques, equipped with field observations and documentation studies. The validity of this research data was checked through triangulation techniques. The results of the study show that the communication strategies implemented are empathetic, participatory, and sustainable, manifested through active listening, the use of everyday language, two-way dialogue, and consistent communicative assistance, thus contributing to the formation of survivors' trust, increasing emotional calm, reducing anxiety, and strengthening social relations and community solidarity. This study recommends strengthening the communication capacity of disaster actors through field-based training, the integration of empathic communication in post-disaster psychosocial recovery guidelines, and the development of assistance policies and practices that are responsive and sensitive to the social, cultural, and psychological context of the affected communities.